Design and Implementation of State-PID Feedback Controller for Poultry House System: Application for Winter Climate - Ilyas Lahlouh; Ahmed Elakkary; Nacer Sefiani (Advances in Science, Technology and Engineering Systems Journal, 2020)
The poultry house is the area where the chickens are maintained for the main purpose to improve the productivity and the environmental conditions for the broilers. The growth of chickens inside the poultry house can be affected by several criterions such as relative humidity and temperature. In this paper, we propose to design and implement experimentally a state-PID feedback controller in order to achieve a high stabilization of the dynamics systems of the poultry process. The purpose of this study is to keep the temperature and relative humidity at desired values and to eliminate the disturbance generated during the winter climate. The effectiveness of the proposed controller is evaluated through numerical examples and with an experimental poultry house prototype. To feature more the efficiency of the proposed approach implemented, a comparative study has been conducted between the results achieved by the proposed method and the state-PI feedback controller and that of a state feedback controller.
Keywords: State-PID feedback controller; Poultry house; Disturbance; Stability analysis